Revolutionizing radical prostatectomy - a comparative study of traditional and modern automated surgical techniques - Rojek, Katarzyna; Szala-Czerwonka, Karolina; Rejmer, Adrian; Woś, Natalia; Bednarz, Lucjan; Wijas, Karolina; Bialic, Kinga; Bakalarczyk, Rafał; Bialic, Artur; Majewski, Paweł (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Prostate cancer is a common malignancy seen worldwide and second most common cancer among Polish men as well as globally. The symptoms of prostate cancer depend on severity of the cancer. Prostate cancer diagnosis is typically established through physical examination- digital rectal examination (DRE), PSA (prostate specific antigen) testing and confirmed by histopathological examination. The choice of treatment method depends on many factors: disease severity, risk assessment (based on PSA, TNM and Gleason score), age of the patient and expected survival time. Treatment include surgery, hormone therapy, radiation therapy or chemotherapy. In some cases, the combination of methods can be used to achieve better outcomes. One of available treatment option is radical prostatectomy which includes open radical prostatectomy (ORP), laparoscopic and laparoscopic robot assisted radical prostatectomy (RARP). We aimed at presenting various outcomes comparing open radical prostatectomy and robot assisted radical prostatectomy. State of knowledge: In order to carry out the review of the topic we began to collect information and comprehensive research in PubMed database. The analysis focused on the treatment of prostate cancer especially radical prostatectomy methods, the course of surgical procedure, postoperative care, oncological results, intraoperative and postoperative complications. Conclusion: ORP and RARP ae two surgical procedures used in prostate cancer treatment. Both of them involve removal of the prostate gland but also have a multiplicity of differences. RARP is safe and less invasive alternative to ORP with shorter postoperative hospitalization. However, ORP is known for no necessity for expensive specialized equipment such as Da Vinci or Versius robot surgery system and shorter operative time.